Late capitalism - Mandel, Ernest (London ; New York : Verso, 1980)
Represents the first ever attempt to combine the general theory of Marx's 'laws of motion' of the capitalist mode of production, with the concrete history of capitalism in the twentieth century.
A translation with revisions of Der Spt̃kapitalismus.
Includes bibliographical references and index.
ENH
Keywords: Capitalism; Economic history -- 1945-; English language